SUPPORT, ACCESS AND ANTENATAL CARE TO WOMEN WITH A HISTORY OF PREECLAMPSIA IN PREGNANCY - Rospia, Evi Diliana; Astuti, Andari Wuri; Mawarti, Retno (Jurnal Kesehatan - STIKes Prima Nusantara, 2020)
Background: Preeclampsia and eclampsia are the second direct cause of maternal death worldwide, estimated to complicate 2-8% of all pregnancies, the global prevalence of preeclampsia is around 4.6%. The purpose of this scoping review is to provide an overview of studies related to antenatal support, access, and services to mothers with a history of preeclampsia in pregnancy. Method: the authors identify studies that explain preeclampsia in pregnancy from several databases, namely PubMed, ProQuest, EBSCO, and Springer Link. Searches are limited to studies published in English and present data for the 2009-2019 period. The identified research was reviewed using the PRISMA Flowchart. Studies with qualitative and quantitative designs that explore the experiences of pregnant women regarding antenatal support, access, and services were selected for review. In contrast, studies that were not experience related to prenatal support, access, and services to mothers with a history of preeclampsia in pregnancy were excluded. Results: A total of twelve articles were reviewed, which obtained three sub-themes of support, namely the support of husband, family, and health workers, from the theme of access obtained three sub-themes, namely information search, modification programs and the availability of health workers. From the idea of antenatal care, four sub-themes are found, namely unsustainable care, lack of information, screening, and feeling empowered. Conclusion: Pregnant women with preeclampsia need support from a partner or family and health workers. Information and screening need to be improved in antenatal care.